2000
DOI: 10.1038/oby.2000.54
|View full text |Cite
|
Sign up to set email alerts
|

Does Weight Loss Maintenance Become Easier Over Time?

Abstract: KLEM, MARY L., RENA R. WING, WEI LANG, MAUREEN T. MCGUIRE, AND JAMES O. HILL. Does weight loss maintenance become easier over time ? Obes Res. 2000;8:438 -444. Objective: Studies of health-related behaviors, including weight loss, have shown that risk of relapse decreases over time, although reasons for this relationship are unclear. The purpose of this cross-sectional study was to determine if subjects who have maintained weight losses for varying periods of time report different strategies for weight loss m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 20 publications
4
44
0
4
Order By: Relevance
“…Over the 2-year period, average weight regain was 5.0 F 7.7 kg [note: this regain is higher than in previous NWCR reports because the sample was limited to partic ipants with shorter durations (5 years or less) who are more likely to regain] [17,21]. A significant trigger group � time interaction was observed ( P = 0.003), even after controlling for age, BMI, gender, initial weight loss, and history of obesity-related medical comorbidity ( P = 0.001).…”
Section: Weight Maintenancementioning
confidence: 57%
“…Over the 2-year period, average weight regain was 5.0 F 7.7 kg [note: this regain is higher than in previous NWCR reports because the sample was limited to partic ipants with shorter durations (5 years or less) who are more likely to regain] [17,21]. A significant trigger group � time interaction was observed ( P = 0.003), even after controlling for age, BMI, gender, initial weight loss, and history of obesity-related medical comorbidity ( P = 0.001).…”
Section: Weight Maintenancementioning
confidence: 57%
“…33 For example, among NWCR participants, those who had maintained weight loss for a shorter length of time, that is, 2-3 years, reported that it required significantly more effort and attention compared to those who had maintained for 6 years or longer. 34 Slips in behavior are frequent and interrupt the learning process, 35,36 thus it is not surprising that weight regain is most likely to happen within the first few years of weight loss. Changes in dietary and physical activity patterns may be particularly difficult to sustain because the behaviors are often time consuming and in opposition to a busy lifestyle built around convenience, mechanization and consumption of energy-dense food.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][17][18][19][20][21][22][23][24]33 Most people who lose weight do so without clinical treatment, 20,31,34 and as such, the prevalence estimates of weight regain in this study on a nationally representative sample may be more indicative of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…People who maintain weight loss longer report that less effort and attention are required to maintain weight loss. 23 Over time, the acquisition of critical behaviors or skills may protect against relapse. 23 Attempting to control weight was also associated with weight regain, although the lack of information on a temporal relationship in this cross-sectional study precludes a causal interpretation.…”
Section: Discussionmentioning
confidence: 99%